First report of the B biotype of Bemisia tabaci (Homoptera: Aleyrodidae) in Colombia - QUINTERO, CONSTANZA; CARDONA, CÉSAR; RAMÍREZ, DARÍO; JIMÉNEZ, NORA (Revista Colombiana de Entomología, 1998)
The presence of the Bemisia tabaci (Gennadius) B biotype was confirmed in Colombia by means of biochemical, molecular, and etiological tests. The biochemical identification consisted of the determination of non-specific esterase banding patterns. Polymorphism among samples collected in Córdoba, Sucre, Atlántico, Valle del Cauca, and Cundinamarca was found, and almost all of the samples were identified as the B biotype, by comparison with A biotype samples drawn from a colony maintained at CIAT for several years. A high degree of polymorphism was found in the B biotype, which was widespread in the area, attacking 23 species of crop plants and 11 weeds. The similarity between a/B esterase patterns of the two biotypes was only 20%. At the molecular level, RAPD amplification products obtained with the primers OPA-04, OPA-11 and OPA-17 were also found to be different between biotypes A and B. Furthermore, after feeding the two biotypes en four cucurbit species, the silver leaf symptom was induced only on Cucurbita moschata (Duchesne) by B biotype nymphs, 21 days after the infestation. The B biotype was found to be more aggressive since it successfully colonized C. mixta Pang., C. pepo L., C. ficifolia Bouché y C. moschata, 23 to 33% faster than biotype A.